Dinâmica de manchas nos sistemas planetários Kepler-9 e Kepler-30 - Gomes, Fernando Oliveira da Silva (2024)
The Kepler-9 and Kepler-30 systems are made of a solar-like star hosting 3 exoplanets. In particular, these systems are highly interesting because starspots produce characteristic light perturbations when occulted by the orbiting planets transiting the host star. We use about 4 years of high-precision photometry collected by the Kepler mission to investigate the flux fluctuations caused by photospheric convection, stellar rotation, and the effect of starspot evolution as a function of the timescale. In this thesis, we model the flux rotational modulation induced by active regions using spot modeling and apply multiple analysis methods: Lomb-Scargle periodogram, magnetic activity, and variability indicators, the Multifractal Detrending Moving Average algorithm (MFDMA), and Spot Modeling. These tools allow an analysis of the behavior of variability and light fluctuations on different timescales. Our results show that the SAP time series is richer in variability than that produced by the PDC pipeline. Furthermore, the light fluctuations caused by the rotational modulation can be described by a simple standard deviation because it provides a measure of the signal-noise ratio. Finally, these procedures and methods may be greatly useful for analyzing data from the still active TESS (Transiting Exoplanet Survey Satellite) and future data from PLATO (Planetary Transits and Oscillations of Stars) mission.